2007
DOI: 10.3727/096368907783338190
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Cells

Abstract: Heart failure is by far the most common cause of hospitalization in Western countries, with onerous economic consequences. Cell therapy holds great promise for use in tissue regeneration and is increasingly used in an effort to improve outcomes in cardiac disease. Recently it has been shown that adipose tissue, in addition to committed adipogenic, endothelial progenitor cells and pluripotent vascular progenitor cells, also contains multipotent cell types (adipose-derived stem cells, ADSCs) that, in cell cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(92 citation statements)
references
References 46 publications
1
88
0
3
Order By: Relevance
“…At pasminimal morbidity in several regions of the body and, on average, 100 ml of human adipose tissue yields about sage 4, cASCs show a fibroblast-like morphology commonly found in mesenchymal stem cell (MSCs). The 1 × 10 6 stem cells (14). In dogs, the adipose tissue can be collected by a simple adapted liposuction surgery, analysis of the cell surface markers showed that the cASCs cell population expresses the known immnophethrough biopsies or in routine veterinary surgery procedures because we could isolate cASCs from just 100 µl notype of MSCs (35).…”
Section: Multilineage Differentiation Casc Isolation and Expansionmentioning
confidence: 99%
“…At pasminimal morbidity in several regions of the body and, on average, 100 ml of human adipose tissue yields about sage 4, cASCs show a fibroblast-like morphology commonly found in mesenchymal stem cell (MSCs). The 1 × 10 6 stem cells (14). In dogs, the adipose tissue can be collected by a simple adapted liposuction surgery, analysis of the cell surface markers showed that the cASCs cell population expresses the known immnophethrough biopsies or in routine veterinary surgery procedures because we could isolate cASCs from just 100 µl notype of MSCs (35).…”
Section: Multilineage Differentiation Casc Isolation and Expansionmentioning
confidence: 99%
“…Adipose-derived stem cells demonstrate clear advantages over BMSCs in availability, yet in vitro cell culture increases the risk of immunogenicity, genetic instability, and infection [16][17][18][19][20][21]. To circumvent these risks, interest has risen in the use of the noncultured stromal vascular fraction (SVF) of adipose tissue among such companies as IntelliCell (New York, NY, http:// www.intellicellbiosciences.com) and Cytori Therapeutics, Inc. (San Diego, CA, http://www.cytori.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies substantiated the therapeutic potential of ADSC by transplanting them in a setting of chronic heart failure [41] or Acute Myocardial Infarction (AMI). After cell transplantation into the myocardial scar tissue in rabbit and porcine models, ADSC formed cardiac islands and vessel-like structures, induced angiogenesis and improved cardiac function with no report of potentially severe arrhythmias [42,43]. The APOLLO trial, a "firstin-man", prospective, double blind, randomized and placebo-controlled trial, demonstrated the safety and feasibility of ADSC transplantation in patients with acute myocardial infarction [43].…”
Section: Discussionmentioning
confidence: 99%